PERAN ORANG TUA SEBAGAI FASILITATOR MEDIATOR MOTIVATOR DALAM MENINGKATKAN KEMANDIRIAN ANAK TUNAGRAHITA SEDANG TINGKAT SMP DI SLB NEGERI BANGKINANG KOTA - Sari, Ella Mutiara; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Role of Parents as Facilitators Motivating Mediators in Increasing the Independence of Moderately Mentally Retarded Children at Junior High School Level in SLB Special Public School Bangkinang City. This research was conducted in Bangkinang District. The purpose and objectives of this research is to find out how the role of parents as facilitators, mediators and motivators in increasing the independence of mentally retarded children at Junior High School Level in SLB Special Public School Bangkinang City. This study used a descriptive qualitative method and the selection of informants used of purposive sampling technique. The subjects in this study were 6 parents of moderately mentally reterded children and 1 teacher who taught mentally reterded children. The data collection technique used was observation, interviews and documentation. The results of the study show that the role of parents as facilitators, mediators, and motivators in increasing the independence of mentally reterded children is parents must provide the best facilities for children to support children’s independence such as providing learning equipment, as mediators parents play a role and take part in teaching children at home, and as motivators parents play a role in giving enthusiasm and positive words to children and always appreciate what children. Keywords: Role of Parents, Independence, Moderate Mentally Disability